Penilaian Kinerja Dosen Menggunakan Metode Simple Additive Weighting (SAW) - Valerian, Kumara Davin; Anas, Muhamad Abdul; Farrasanto, Akram; Raehan, Muhamad; Anshor, Abdul Halim (Jurnal Kridatama Sains dan Teknologi, 2024)
Lecturer performance evaluation is an important component in efforts to improve the quality of education, research, and community service in higher education. Effective lecturer performance depends not only on academic competence, but also on pedagogical ability, discipline, and contribution to the development of science and technological innovation. This study aims to design a decision support system based on the Simple Additive Weighting (SAW) method to produce objective and measurable lecturer performance. Research data were collected through observation by reviewing the head of the study program and informatics engineering students at Pelita Bangsa University. The evaluation process includes normalizing the decision matrix that includes several main criteria, such as attendance, discipline, course learning objectives, and semester learning plans. Each criterion is given a weight according to its level of importance. The results of the alternative calculations show that the highest score is selected as the contribution with the best performance. In this study, data from 20 doses were analyzed, resulting in a ranking based on the calculated scores. The second alternative (TIF2) obtained the highest score (V2 = 0.95), followed by the fifth alternative (TIF5) with a score (V5 = 0.94). These findings indicate that the SAW method can efficiently identify the best dose performance based on predetermined criteria. This system not only provides objective results but also facilitates the decision-making process in higher education institutions. The system designed through this research is expected to be an effective tool in transmitting and improving lecturer performance. With proper implementation, universities can improve the quality of teaching, research, and community service sustainably